The Effect of Welding Speed on the Welding Quality AISI 1020 and AISI 1050 Steel Using Shielded Metal Arc Welding Technology - Syaipudin Anwar; Nanda Tri Wiranata Nanda; Tarkono Tarkono; Sugiyanto Sugiyanto; A Yudi Eka Risano Yudi (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2025)
Material joining techniques are divided into two categories: similar joints and dissimilar joints. The difference in thermal cycles experienced by each material is the reason why dissimilar welding is more challenging than similar welding. The welding process that joins two materials with different properties is commonly used to improve effectiveness and efficiency in production, as well as to improve product quality. This trend has become popular in the manufacturing industry, including in the manufacture of tailor welded blanks, transportation vehicle frames such as aircraft, trains, and cars, as well as in the manufacture of public and private vehicle accessories such as aircraft panels and exhausts. The materials currently widely used in exploration are stainless steel combined with carbon steel, as well as a mixture of stainless steel and low carbon steel, which is quite challenging to weld but offers the advantages of higher strength, corrosion resistance, and lighter weight. This challenge can be overcome through liquid welding methods, one of which is the